Health policy considerations for combining exercise prescription into noncommunicable diseases treatment: a narrative literature review - Tao, Dan; Awan-Scully, Roger; Ash, Garrett I.; Gu, Yaodong; Pei, Zhong; Gao, Yang; Cole, Alistair; Supriya, Rashmi; Sun, Yan; Xu, Rui; Baker, Julien S. (Frontiers in Public Health, 2023)
Objectives In this review, we aim to highlight the evidence base for the benefits of exercise in relation to the treatment of noncommunicable diseases (NCDs), draw on the Health Triangular Policy Framework to outline the principal facilitators and barriers for implementing exercise in health policy, and make concrete suggestions for action. Methods Literature review and framework analysis were conducted to deal with the research questions. Results Exercise prescription is a safe solution for noncommunicable diseases prevention and treatment that enables physicians to provide and instruct patients how to apply exercise as an important aspect of disease treatment and management. Combining exercise prescription within routine care, in inpatient and outpatient settings, will improve patients’ life quality and fitness levels. Conclusion Inserting exercise prescription into the healthcare system would improve population health status and healthy lifestyles. The suggestions outlined in this study need combined efforts from the medical profession, governments, and policymakers to facilitate practice into reality in the healthcare arena.